THE EFFECTIVENESS OF DIGITAL MARKETING IN INCREASING THE MARKETING OF LEGENDAR CRACKERS PRODUCTS IN SAWANGAN - Herliana Rizki Yati; Saryadi (Sekolah Tinggi Agama Islam Syubbanul Wathon Magelang, 2022)
Most MSMEs in rural areas utilize and increase the value of local raw materials to produce a product. Utilization of local raw materials as superior products for SMEs is carried out in particular in the Sawangan Hamlet, Sawangan Village Magelang Regency. One of the SMEs that utilizes local raw materials is the centre for making Gendar crackers. Products produced from these raw materials are very popular with traditional ones. However, good marketing has yet to support the amount of product produced. This is due to the need for more marketing personnel and the absence of a food product brand. Based on this, the servant assists the MSMEs in marketing strategies. In assisting marketing activities, the servants assist by providing training on the use of social media as a marketing tool and making product labels or brands that become the identity of the Gendar Cracker snack product from Sawangan hamlet.